From East and West: A Shifting Cultural Landscape of Natural Health Products. 11th Annual Conference presented by Natural Health Product Research Society of Canada, in conjunction with the Canadian Institute of Chinese Medicinal Research - Beverley Berekoff (Frontiers Media S.A., 2014)
Proceedings of 2014 conference presented by Natural Health Product Research Society of Canada, in conjunction with the Canadian Institute of Chinese Medicinal Research.  May 13 - 16, 2014, Kelowna, BC, Canada